# Square of Identities Involving Squares of Sines and Cosines

We will learn how to solve identities involving square of sines and cosines of multiples or submultiples of the angles involved.

We use the following ways to solve the identities involving square of sines and cosines.

(i) Express the first two squares of L.H.S. in terms of cos 2A (or cos A).

(ii) Either retain the third term unchanged or make a change using the formula sin$$^{2}$$ A+ cos$$^{2}$$ A = 1.

(iii) Keeping the numericais (if any) apart, express the sum of two cosines in the form of product.

(iv) Then use the condition A + B + C = π (or A + B + C = $$\frac{π}{2}$$)and take one sine or cosine term common.

(v) Finally, express the sum or difference of two sines (or cosines) in the brackets as product.

1. If A + B + C = π, prove that,

cos$$^{2}$$ A + cos$$^{2}$$ B - cos$$^{2}$$ C = 1 - 2 sin A sin B cos C.

Solution:

L.H.S. =  cos$$^{2}$$ A + cos$$^{2}$$ B - cos$$^{2}$$ C

= cos$$^{2}$$ A + (1 - sin$$^{2}$$ B) - cos$$^{2}$$ C

= 1 + [cos$$^{2}$$ A - sin$$^{2}$$ B] - cos$$^{2}$$ C

= 1 + cos (A + B) cos (A - B) - cos$$^{2}$$ C

= 1 + cos (π - C) cos (A - B) - cos$$^{2}$$ C, [Since A + B + C = π ⇒ A + B = π - C]

= 1 - cos C cos (A - B) - cos$$^{2}$$ C

= 1 - cos C [cos (A - B) + cos C]

= 1 - cos C [cos (A - B) + cos {π - (A + B)}], [Since A + B + C = π ⇒ C = π - (A + B)]

= 1 - cos C [cos (A - B) - cos (A + B)]

= 1 - cos C [2 sin A sin B]

= 1 - 2 sin A sin B cos C = R.H.S.                    Proved.

2. If A + B + C = π, prove that,

sin$$^{2}$$ $$\frac{A}{2}$$ + sin$$^{2}$$ $$\frac{A}{2}$$ + sin$$^{2}$$ $$\frac{A}{2}$$ = 1 - 2 sin $$\frac{A}{2}$$ - sin $$\frac{B}{2}$$ sin $$\frac{C}{2}$$

Solution:

L.H.S. = sin$$^{2}$$ $$\frac{A}{2}$$ + sin$$^{2}$$ $$\frac{B}{2}$$ + sin$$^{2}$$ $$\frac{C}{2}$$

= $$\frac{1}{2}$$(1 - cos A) + $$\frac{1}{2}$$(1 - cos B) + sin$$^{2}$$ $$\frac{C}{2}$$, [Since, 2 sin$$^{2}$$ $$\frac{A}{2}$$ = 1 - cos A

⇒ sin$$^{2}$$ $$\frac{A}{2}$$ = $$\frac{1}{2}$$(1 - cos A)

Similarly, sin$$^{2}$$  $$\frac{B}{2}$$ = $$\frac{1}{2}$$( 1 - cos B)]

= 1 - $$\frac{1}{2}$$(cos A + cos B) + sin$$^{2}$$ $$\frac{C}{2}$$

= 1 -  $$\frac{1}{2}$$ ∙ 2 cos $$\frac{A + B}{2}$$  ∙ cos $$\frac{A - B}{2}$$ + sin$$^{2}$$ $$\frac{C}{2}$$

=1 - sin $$\frac{C}{2}$$  cos $$\frac{A - B}{2}$$  + sin 2 $$\frac{C}{2}$$

[A + B + C = π ⇒ $$\frac{A + B}{2}$$ = $$\frac{π}{2}$$  - $$\frac{C}{2}$$.

Therefore, cos $$\frac{A + B}{2}$$ = cos ($$\frac{π}{2}$$  - $$\frac{C}{2}$$) = sin $$\frac{C}{2}$$]

= 1 - sin $$\frac{C}{2}$$[cos $$\frac{A - B}{2}$$ - sin $$\frac{C}{2}$$]

= 1 - sin $$\frac{C}{2}$$[cos $$\frac{A - B}{2}$$ - cos $$\frac{A + B}{2}$$]   [Since, sin $$\frac{C}{2}$$ = cos $$\frac{A + B}{2}$$]

= 1 - sin $$\frac{C}{2}$$[2 sin $$\frac{A}{2}$$ ∙ sin $$\frac{B}{2}$$]

= 1 - 2 sin $$\frac{A}{2}$$ sin $$\frac{B}{2}$$ sin $$\frac{C}{2}$$ = R.H.S.                    Proved.

3. If A + B + C = π, prove that,

cos$$^{2}$$  $$\frac{A}{2}$$  + cos$$^{2}$$ $$\frac{B}{2}$$ - cos$$^{2}$$ $$\frac{C}{2}$$  = 2 cos $$\frac{A}{2}$$ cos $$\frac{B}{2}$$  sin $$\frac{C}{2}$$

Solution:

L.H.S. = cos$$^{2}$$  $$\frac{A}{2}$$  + cos$$^{2}$$ $$\frac{B}{2}$$ - cos$$^{2}$$ $$\frac{C}{2}$$

= $$\frac{1}{2}$$(1 + cos A) + $$\frac{1}{2}$$(1 + cos B) - cos$$^{2}$$ $$\frac{C}{2}$$, [Since, 2 cos$$^{2}$$ $$\frac{A}{2}$$  = 1 + cos A  ⇒ cos$$^{2}$$ $$\frac{A}{2}$$ = $$\frac{1}{2}$$(1 + cos A)

Similarly, cos$$^{2}$$ $$\frac{B}{2}$$ = $$\frac{1}{2}$$(1 + cos B)]

=  1 + $$\frac{1}{2}$$(cos A + cos B) - cos$$^{2}$$ $$\frac{C}{2}$$

= 1 + $$\frac{1}{2}$$ ∙ 2 cos $$\frac{A + B}{2}$$ cos $$\frac{A - B}{2}$$ - 1 + sin$$^{2}$$  $$\frac{C}{2}$$

= cos $$\frac{A + B}{2}$$ cos $$\frac{A - B}{2}$$ + sin$$^{2}$$  $$\frac{C}{2}$$

= sin C/2 cos $$\frac{A - B}{2}$$ + sin$$^{2}$$  $$\frac{C}{2}$$

[Since, A + B + C = π ⇒ $$\frac{A + B}{2}$$  = $$\frac{π}{2}$$ - $$\frac{C}{2}$$.

Therefore, cos ($$\frac{A + B}{2}$$) = cos ($$\frac{π}{2}$$ - $$\frac{C}{2}$$) = sin $$\frac{C}{2}$$]

= sin $$\frac{C}{2}$$ [cos $$\frac{A - B}{2}$$ + sin $$\frac{C}{2}$$]

= sin $$\frac{C}{2}$$ [cos $$\frac{A - B}{2}$$ + cos $$\frac{A + B}{2}$$], [Since, sin $$\frac{C}{2}$$ = cos $$\frac{A - B}{2}$$]

= sin $$\frac{C}{2}$$ [2 cos $$\frac{A}{2}$$ cos $$\frac{B}{2}$$]

= 2 cos $$\frac{A}{2}$$ cos $$\frac{B}{2}$$ sin $$\frac{C}{2}$$ = R.H.S.          Proved.

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles

1. ### Months of the Year | List of 12 Months of the Year |Jan, Feb, Mar, Apr

Apr 20, 24 05:39 PM

There are 12 months in a year. The months are January, February, march, April, May, June, July, August, September, October, November and December. The year begins with the January month. December is t…

2. ### What are Parallel Lines in Geometry? | Two Parallel Lines | Examples

Apr 20, 24 05:29 PM

In parallel lines when two lines do not intersect each other at any point even if they are extended to infinity. What are parallel lines in geometry? Two lines which do not intersect each other

3. ### Perpendicular Lines | What are Perpendicular Lines in Geometry?|Symbol

Apr 19, 24 04:01 PM

In perpendicular lines when two intersecting lines a and b are said to be perpendicular to each other if one of the angles formed by them is a right angle. In other words, Set Square Set Square If two…

4. ### Fundamental Geometrical Concepts | Point | Line | Properties of Lines

Apr 19, 24 01:50 PM

The fundamental geometrical concepts depend on three basic concepts — point, line and plane. The terms cannot be precisely defined. However, the meanings of these terms are explained through examples.